Analysis of Endophytic Bacterial Diversity From Different Dendrobium Stems and Discovery of an Endophyte Produced Dendrobine-Type Sesquiterpenoid Alkaloids - Wang, Shan-Shan; Liu, Jia-Meng; Sun, Jing; Huang, Ya-Tao; Jin, Nuo; Li, Min-Min; Liang, Yan-Tian; Fan, Bei; Wang, Feng-Zhong (Frontiers in Microbiology, 2022)
As the unique component of Dendrobium, Dendrobine-type Sesquiterpenoid Alkaloids (DSAs) possess a variety of medicinal properties. It has been well documented that plant endophytes can in vitro synthesize secondary metabolites identical or similar to metabolites produced by their host plants. The aim of this study was to investigate the composition and distribution of endophytic bacteria of Dendrobium stems by Illumina MiSeq platform sequencing and cultivation-dependent methods, and then to assess the potential for endophytic bacteria to produce DSAs. Results indicated that it was necessary to combine both cultivation-dependent and cultivation-independent methods to analyze the community structure of endophytic bacterial in plants comprehensively. The endophytic bacterial community was influenced by the length of the Dendrobium stems. The diversity and richness of endophytic bacteria in Group J10_15cm of stems were the highest, which showed significantly difference from the other stem groups. However, there was no certain connection between the diversity and richness of endophytic bacteria and the content of dendrobine. It was most likely due to the influence of several specific endophytic bacteria genera, such as Sphingomonas and Rhodococcus. Athelia rolfsii, Myrothecium roridum as pathogenic fungi, and Pectobacterium carotovorum subsp. actinidiae as pathogenic bacteria of Dendrobium, were used to determine the antimicrobial activities. In these assays, six strains belonged to 5 genera showed antimicrobial activity against at least two phytopathogens. The strain BL-YJ10_15-29 (Paracoccus pueri THG-N2.35, 98.98%) showed the best antimicrobial activity against the three phytopathogens. In addition, 2 DSAs (6-hydroxydendrobine and nobilonine) were identified in the fermentation supernatant of the strain CM-YJ10_15-44 (Pseudomonas protegens CHA0, 99.24%), while the whole genome analysis results further demonstrated that the precursors of the two DSAs (Geranyl-PP and (E, E)-Famesyl-PP) were synthesized mainly through the methyl-D-erythritol 4-phosphate (MEP) pathway in this strain. This study provides a new insight into the studies on biosynthesis of DSAs and provides potential biocontrol bacteria.